2017
DOI: 10.7150/jca.18626
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA CCAT2 as a Potential Novel Biomarker to Predict the Clinical Outcome of Cancer Patients: A Meta-Analysis

Abstract: Background: Colon Cancer-Associated Transcript 2 (CCAT2) has been demonstrated associated with clinical outcomes in various tumors. However, the results from each study were unfortunately insufficient and not completely consistent. Therefore, we conduct a systematic meta-analysis to evaluate the value for a feasible biomarker for metastasis and prognosis.Methods: A meta-analysis was performed using data obtained through a systematic search of PubMed, EMBASE, Cochrane Library, China National Knowledge Infrastru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Additionally, the elevated CCAT2 expression was also considerably correlated with LNM, DM, and tumor stage. Furthermore, results of several other meta-analyzes on CCAT2 [37–40] have revealed similar results. Therefore, high CCAT2 expression is a predictor of unfavorable DM, LNM, PFS, OS, and later tumor stages [Supplementary Figures 1–8, http://links.lww.com/CM9/B423].…”
Section: Meta-analysis Of Ccat2supporting
confidence: 61%
“…Additionally, the elevated CCAT2 expression was also considerably correlated with LNM, DM, and tumor stage. Furthermore, results of several other meta-analyzes on CCAT2 [37–40] have revealed similar results. Therefore, high CCAT2 expression is a predictor of unfavorable DM, LNM, PFS, OS, and later tumor stages [Supplementary Figures 1–8, http://links.lww.com/CM9/B423].…”
Section: Meta-analysis Of Ccat2supporting
confidence: 61%
“…In our study, low SNCG expression was significantly associated with reduced OS in MBC patients (p = 0.049, log-rank), while Wu et al reported that SNCG-positive patients showed a significantly poorer prognosis than SNCG-negative patients 32 . Low CCAT2 expression was significantly associated with decreased OS (p = 0.023, log-rank) in NMBC patients, while Tan et al found that CCAT2 was significantly correlated with OS and progression-free survival 54 .…”
Section: Discussionmentioning
confidence: 98%
“…Recently, lncRNA has been shown to participate in the initiation, development and progression in different cancers and has raised researchers' interest in last consecutive years. Among them, some lncRNAs including CCAT2, SNHG16, and GIHCG, could function as tumor oncogenes and facilitate tumorigenesis or tumor progression [40][41][42], while other lncRNAs such as BLACAT1, NORAD, NEF are well established as tumor suppressors [43][44][45].…”
Section: Discussionmentioning
confidence: 99%